miR-222 Is Involved in the Amelioration Effect of Genistein on Dexamethasone-Induced Skeletal Muscle Atrophy - Mailin Gan (Nutrients, 2022)
Skeletal muscle atrophy is a complex degenerative disease characterized by decreased skeletal muscle mass, skeletal muscle strength, and function. MicroRNAs (miRNAs) are a potential therapeutic target, and natural products that regulate miRNA expression may be a safe and effective treatment strategy for muscle atrophy. Previous studies have shown beneficial effects of genistein treatment on muscle mass and muscle atrophy, but the mechanism is not fully understood. Differential co-expression network analysis revealed that miR-222 was upregulated in multiple skeletal muscle atrophy models. Subsequent in vitro (C2C12 myoblasts) and in vivo (C57BL/6 mice) experiments showed that genistein could alleviate dexamethasone-induced muscle atrophy and downregulate the expression of miR-222 in muscle tissue and C2C12 myotubes. The dual-luciferase reporter assay system confirmed that IGF1 is a target gene of miR-222 and is regulated by genistein. In C2C12 myotubes, both dexamethasone and miR-222 overexpression promoted muscle atrophy, however, this function was significantly reduced after genistein treatment. Furthermore, we also observed that both genistein and miR-222 antagomiR could significantly inhibit dexamethasone-induced muscle atrophy in vivo. These results suggest that miR-222 may be involved in the regulation of genistein on muscle atrophy, and genistein and miR-222 may be used to improve muscle health.